2020
DOI: 10.1149/1945-7111/ab7e20
|View full text |Cite
|
Sign up to set email alerts
|

A Very Simple Method for Detection of Bisphenol A in Environmental Water by Heme Signal Amplification

Abstract: The detection of bisphenol A (BPA) was carried out using several simplified electrochemical sensors in which electroactive materials Heme, dopamine (DA), β-cyclodextrins (β-CD) or Fc-ECG were deposited on screen-printed electrodes (SPEs) through one-step. The preparation of the developed sensors were verified by SEM, CV and DPV. Results shown that Heme/SPE sensor demonstrated notable electro-catalytic capabilities and a greater current response than other sensors for BPA detection and optimal operating conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…1 In addition, several groups have performed the electrochemical detection of 4-NP alone using modified electrodes with various nanocomposites consisting of gold− zinc sulfide nanocomposite nanorods, 13 carbohydrate-derived nitrogen-doped hierarchical porous carbon, 14 and ultrathin sulfur-doped graphitic carbon nitride nanosheets. 15 Moreover, Arfin et al 16 used a graphene oxide−zinc oxide nanocomposite for the detection of phenol, while Bolat et al 17 and Feng et al 18 reported a poly(cetyltrimethylammonium bromide)multiwalled carbon nanotube-based composite and hememodified screen printed electrodes, respectively, that can only detect BPA. There are only a few studies that have used nanocomposites comprising polyaniline and magnetite nanorods for the simultaneous electrochemical detection of phenolic pollutants.…”
Section: ■ Introductionmentioning
confidence: 99%
“…1 In addition, several groups have performed the electrochemical detection of 4-NP alone using modified electrodes with various nanocomposites consisting of gold− zinc sulfide nanocomposite nanorods, 13 carbohydrate-derived nitrogen-doped hierarchical porous carbon, 14 and ultrathin sulfur-doped graphitic carbon nitride nanosheets. 15 Moreover, Arfin et al 16 used a graphene oxide−zinc oxide nanocomposite for the detection of phenol, while Bolat et al 17 and Feng et al 18 reported a poly(cetyltrimethylammonium bromide)multiwalled carbon nanotube-based composite and hememodified screen printed electrodes, respectively, that can only detect BPA. There are only a few studies that have used nanocomposites comprising polyaniline and magnetite nanorods for the simultaneous electrochemical detection of phenolic pollutants.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Our group previously reported that the Heme/SPE sensor enhanced current responses for UA, AA, DA and BPA catalysis due to the electrocatalytic ability of heme. 23,24 As . Additional analyses examining the ability for detection of NO 2 À and S 2 O 3 2À were consequently undertaken.…”
Section: Detection Of Nomentioning
confidence: 99%
“…Therefore, it is important to find the right modifier. Heme plays an important role in the construction of many sensors because that Heme can amplify the signal of the detected substances [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%